Digital multimodal composing: A synthesis of theory-research connections and justifications for task selection - Kessler, Matt (Studies in Second Language Learning and Teaching, 2026)
As human communications have grown increasingly digital and multimodal, so too, has scholarly interest in the topic of digital multimodal composing (DMC). Much research to date has explored various aspects of DMC tasks, including their capacity to affect second language (L2) learning processes and outcomes in the classroom. Despite this, two recurring limitations have surfaced across studies, which involve: (1) unclear connections between theory and research designs, and (2) missing justifications as to why a DMC task or activity was used in the study context. The current article opens with a brief overview of DMC literature, followed by a discussion of these limitations. To further explore their pervasiveness, a research synthesis was conducted of DMC studies published since 2023 (K = 42). The findings of this synthesis show that although researchers often mention theory in their introduction and literature review sections, theory is rarely tied to an aspect of the research methods (e.g., instrument design, data analyses). Additionally, less than one-third of the studies reviewed contain explanations as to why a specific DMC task was adopted. Based on these findings, future recommendations are provided with the aim of fostering stronger connections between theory, research, and practice.